THE THE EFFECT OF ABDURRAB UNIVERSITY LIBRARY WEBSITE QUALITY ON USER SATISFACTION USING MULTIPLE LINEAR REGRESSION AND IMPORTANCE PERFORMANCE ANALYSIS - Dasri Surya Hamdani; Muhammad Jazman; Muhammad Luthfi Hamzah; Anofrizen Anofrizen (Jurnal Teknik Informatika (Jutif), 2022)
Abdurrab University library website is an effort to improve services in providing information in the form of physical book data and digital collections to its users. This study aims to analyze the influence of the quality of the Abdurrab University library website on user satisfaction based on end user perceptions. The WebQual 4.0 method was modified by the researcher with the addition of the variables user interface quality and the quality of reliability to compile this research instrument. The distribution of questionnaires was carried out online and offline to 96 respondents obtained from the results of sample calculations using the slovin formula from a total population of 2552 people. The quality of Abdurrab University library website based on multiple linear regression analysis partially variables Usability Quality and The Quality of Reliability affect user satisfaction while simultaneously all WebQual 4.0 variable modifications affect user satisfaction. The influence of independent variables on dependent variables received a value of 43.6% and 56.4% was influenced by independent variables that were not used in this study, so the quality of the website was classified as poor. The quality of Abdurrab University library website is based on Importance Performance Analysis (IPA) for conformity level analysis of 85.29% and gap analysis of -0.55, with a conformity level analysis value of 85.29% of websites is good. The conclusion of this study is that the quality of the Abdurrab University library website affects user satisfaction, so this research can be used as a reference for improvement by the Abdurrab University library.